2014
DOI: 10.1038/ncomms5632
|View full text |Cite
|
Sign up to set email alerts
|

Myc inhibition is effective against glioma and reveals a role for Myc in proficient mitosis

Abstract: Gliomas are the most common primary tumours affecting the adult central nervous system and respond poorly to standard therapy. Myc is causally implicated in most human tumours and the majority of glioblastomas have elevated Myc levels. Using the Myc dominant negative Omomyc, we previously showed that Myc inhibition is a promising strategy for cancer therapy. Here, we preclinically validate Myc inhibition as a therapeutic strategy in mouse and human glioma, using a mouse model of spontaneous multifocal invasive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
131
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(147 citation statements)
references
References 31 publications
4
131
0
2
Order By: Relevance
“…USP28 overexpression could deubiquitinate FBW7 ....................................................................................................................... through deubiquitination of their substrates such as MYC, because USP28 is a member of the ubiquitin-specific protease family. 9,22 In this study, USP28 overexpression significantly increased MYC expression, whereas USP28 knockdown produced an opposite effect in glioma cells. The inhibition of MYC by siRNA reversed the induction of USP28 on glioma cell proliferation.…”
Section: Discussionmentioning
confidence: 89%
“…USP28 overexpression could deubiquitinate FBW7 ....................................................................................................................... through deubiquitination of their substrates such as MYC, because USP28 is a member of the ubiquitin-specific protease family. 9,22 In this study, USP28 overexpression significantly increased MYC expression, whereas USP28 knockdown produced an opposite effect in glioma cells. The inhibition of MYC by siRNA reversed the induction of USP28 on glioma cell proliferation.…”
Section: Discussionmentioning
confidence: 89%
“…Mice expressing OmoMYC in a doxycycline-inducible manner display rapid regression of lung adenocarcinomas, glioblastomas and pancreatic tumors but show only mild and fully reversible effects on proliferation in normal tissues 9,17,18 . As consequence, intermittent induction of OmoMYC ("metronomic treatment") enables long-term suppression of tumor growth arguing that therapeutic strategies that mimic OmoMYC may have significant efficacy for the treatment of human tumors 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Among the factors and pathways implicated in glioma development and growth, the kinases phosphoinositide 3-kinase and mitogen-activated protein kinase are among the most studied (Daniel et al, 2014). Annibali et al, (2014) found that Myc inhibition reduces proliferation, increases apoptosis, and, remarkably, elicits the formation of multinucleated cells that then arrest or die by mitotic catastrophe, revealing a new role for Myc in the proficient division of glioma cells. Some results confirmed that PIK3CA mutations occurred in a significant number of human glioblastomas, making it a promising target for therapy, particularly for primary glioblastomas (Weber et al, 2011;Derakhshandeh-Peykar et al, 2012).…”
Section: Discussionmentioning
confidence: 99%